Production of a bioherbicide agent in liquid and solid medium and in a biphasic cultivation system - Moraes,C. (2014)
The use of fungi in weeds control programs depends upon the conidia production in large scale. Therefore, this study aimed to evaluate liquid and solid culture media and the cultivation by biphasic system for the conidia production of Bipolaris euphorbiae Muchovej & Carvalho a specific pathogen of Euphorbia heterophylla. The liquid media were obtained from agro-industrial waste or by-products, and the solid media were prepared with mixtures of grains and grain derivatives. The liquid medium made with sugar cane molasses stood out from the others because it provided great sporulation (23 x 10(4) conidia mL-1 of medium), conidial viability (99.7%), and formation of mycelial fungal biomass (1.26 g 100 mL-1 of medium). On solid media conidial production was markedly higher than in liquid media, especially the medium composed by a blend of sorghum grain (40%) and soybean hulls (60%) where the fungus produced 2.3 x 10(7) conidia g-1 of medium. The cultivation of B. euphorbiae in biphasic system not promoted a significant increase in the production of conidia. The solid media were more effective for the mass production of fungus and mixtures of grains and derivatives were effective for increasing conidia production.